Prion Amyloid Polymorphs – The Tag Might Change It All - Bousset, Luc; Luckgei, Nina; Kabani, Mehdi; Gardiennet, Carole; Schütz, Anne K.; Melki, Ronald; Meier, Beat H.; Böckmann, Anja (Frontiers in Molecular Biosciences, 2020)
Sup35p is a protein from Saccharomyces cerevisiae. It can propagate using a prion-like mechanism, which means that it can recruit non-prion soluble Sup35p into insoluble fibrils.Sup35p is a large protein showing three distinct domains, N, M and an extended globular domain. We have previously studied the conformations of the full-length and truncated NM versions carrying poly-histidine tags on the N-terminus. Comparison with structural data from C-terminally poly-histidine tagged NM from the literature surprisingly revealed discrepancies.Here we investigated fibrils from the untagged, as well as a C-terminally poly-histidine tagged NM construct, using solid-state NMR. We find that the conformation of untagged NM is very close to the N-terminally tagged version and confirms our previous findings. The C-terminal poly-histidine tag, in contrast, drastically changes the fibril structure, and yields data consistent with results obtained previously on this construct. We conclude that not only the Sup35p globular domain influences the structure of the fibrillar core formed by residues from the N domain, but also small tags can, even when localized far from the fibrillar core, do have an unexpected influence on the fibril structure, and its propensity to induce the [PSI+] prion trait.